2019
DOI: 10.3390/e21121224
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Cardiovascular Complexity during Acute Exposure to High Altitude: A Multiscale Entropy Approach

Abstract: Stays at high altitude induce alterations in cardiovascular control and are a model of specific pathological cardiovascular derangements at sea level. However, high-altitude alterations of the complex cardiovascular dynamics remain an almost unexplored issue. Therefore, our aim is to describe the altered cardiovascular complexity at high altitude with a multiscale entropy (MSE) approach. We recorded the beat-by-beat series of systolic and diastolic blood pressure and heart rate in 20 participants for 15 min tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
4
3
0
Order By: Relevance
“…This was evident in the results from the BtB analyses reported herein, which provided mean SampEn values more than double those from the interpolated approach, as shown in Table 1. This is in line with previous cardiovascular entropy studies, which have reported mean SampEn values calculated in BtB data of >1.2; compared with mean sBP SampEn ~1.67 in the present study [23,49,50]. Despite this limitation, SampEn values calculated from both one and five minutes of 5 Hz interpolated data were significantly associated with cognitive performance, whereas SampEn values calculated from the BtB data were not.…”
Section: Discussionsupporting
confidence: 91%
“…This was evident in the results from the BtB analyses reported herein, which provided mean SampEn values more than double those from the interpolated approach, as shown in Table 1. This is in line with previous cardiovascular entropy studies, which have reported mean SampEn values calculated in BtB data of >1.2; compared with mean sBP SampEn ~1.67 in the present study [23,49,50]. Despite this limitation, SampEn values calculated from both one and five minutes of 5 Hz interpolated data were significantly associated with cognitive performance, whereas SampEn values calculated from the BtB data were not.…”
Section: Discussionsupporting
confidence: 91%
“…This conclusion is supported by several studies ( Hughson et al, 1994 ; Perini et al, 1996 ; Saito et al, 2005 ) in which the balance of the ANS shifts toward relatively low parasympathetic and high sympathetic activity at high altitudes. Coherently with our result, a decrease of the heart-rate SampEn was observed during a real high-altitude environment ( Saito et al, 2005 ; Boos et al, 2018 ; Faini et al, 2019 ) and in a simulated high altitude ( Zhang et al, 2015 ). However, Vigo et al (2010) reported the opposite trend in a low-pressure chamber experiment simulating an altitude of 8,230 m asl, reflecting a rapid activation of defensive autonomic responses induced by the subjects’ sudden exposure to an extreme abnormal environment.…”
Section: Discussionsupporting
confidence: 90%
“…These spectral changes are in line with those repeatedly reported on the acute autonomic effects after an ascent at high altitude (Hughson et al, 1994;Perini et al, 1996;Saito et al, 2005;Chen et al, 2008;Faini et al, 2019) or a simulated altitude of 3,600 m asl in a hypobaric/hypoxic chamber. Similarly, Boos et al (2018) found an increase in LF power but without a change in HF power at relatively lower altitudes (3,000 m asl).…”
Section: Significance Of Hrv Changessupporting
confidence: 91%
See 1 more Smart Citation
“…Their results suggest that this entropy measure may distinguish diabetic patients with a satisfactory control of blood glucose from those with poor control, highlighting the feasibility of assessing autonomic dysfunctions of clinical relevance by the percussion entropy. Also Faini et al [ 10 ] considered a second cardiovascular signal in addition to the electrocardiogram: the finger arterial pressure. These authors calculated the multiscale sample entropy of the heart rate series and of the series of systolic and diastolic arterial pressure in volunteers at sea level and at high altitude and explained the alterations observed at high altitude by the increased chemoreflex sensitivity induced by hypoxia.…”
mentioning
confidence: 99%